2017
DOI: 10.1097/qai.0000000000001284
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Clinic Switching Among Postpartum Women Considered Lost to HIV Care in South Africa

Abstract: Objective Retention in HIV care, particularly among postpartum women, is a challenge to national antiretroviral therapy (ART) programs. Retention estimates may be underestimated due to unreported transfers. We explored mobility and clinic switching among patients considered lost to follow-up (LTFU). Design Observational cohort study. Methods Of 788 women initiating ART during pregnancy at six public clinics in Johannesburg, South Africa, 300 (38.1%) were LTFU (no visit ≥3 months). We manually searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 28 publications
(30 reference statements)
4
105
0
Order By: Relevance
“…It is possible that respondents were presenting an optimistic scenario about continuing their care after delivery in order to appeal to the interviewer, a limitation of self‐reported data. We recently found evidence of women continuing HIV care elsewhere in South Africa after initiating ART in Johannesburg, so women may indeed visit a clinic in their “home” area, particularly if their stay is extended. South Africa has a fragmented healthcare system, and the lack of national, networked electronic medical records means that a patient presenting at a new clinic cannot access her records from the first.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that respondents were presenting an optimistic scenario about continuing their care after delivery in order to appeal to the interviewer, a limitation of self‐reported data. We recently found evidence of women continuing HIV care elsewhere in South Africa after initiating ART in Johannesburg, so women may indeed visit a clinic in their “home” area, particularly if their stay is extended. South Africa has a fragmented healthcare system, and the lack of national, networked electronic medical records means that a patient presenting at a new clinic cannot access her records from the first.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that respondents were presenting an optimistic scenario about continuing their care after delivery in order to appeal to the interviewer, a limitation of self-reported data. We recently found evidence of women continuing HIV care elsewhere in South Africa after initiating ART in Johannesburg, [20] so women may indeed and there I won't get the same treatment there that I get here, so I prefer that I continue with the way I am getting treatment now. " -Participant 112, site two "I will have maternity leave for four months and I will go home.…”
Section: Discussionmentioning
confidence: 99%
“…However, these benefits hinge on women initiating ART, adhering to treatment, and remaining in care in the long term. Postpartum retention is a major challenge and there is an urgent need to understand how mobility may contribute to this .…”
Section: Introductionmentioning
confidence: 99%
“…These movements may introduce challenges to the continuum of HIV care and maternal health services . In South Africa, a recent analysis found that 38% of postpartum women who were considered lost to follow‐up (LTFU) at the clinic of ART initiation were in care elsewhere, and 33% received care outside of the province where they started ART . However, there are few data on the mobility of women with mandatory movement of ART care postpartum, and there is a need to understand the specific challenges related to linkage to care and mobility after delivery in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…The model allows for the possibility that individuals may interrupt ART, and also allows for the possibility that ART may be re-initiated after an interruption. Based on recent South African studies [373375], we assume that the annual rate of interrupting ART is 0.25 and the annual rate of resuming ART after an interruption is 0.90. This implies that modelled ART interruptions are frequent but usually of relatively short duration.…”
Section: Hiv Interventionsmentioning
confidence: 99%